2017
DOI: 10.1016/j.xphs.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Do We Need to Study Metabolism and Distribution in the Eye: Why, When, and Are We There Yet?

Abstract: The liver is known to be the principal site of drug metabolism. Depending on the route of administration, especially in cases of topical and local delivery, evaluation of local drug metabolism in extrahepatic tissues is vital to assess fraction of the drug metabolized. This parameter becomes important from the point of view of drug availability or the contribution to overall clearance. Examples include fraction metabolized in the gut for oral drugs and contribution of pulmonary or renal clearance to total clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…During ophthalmic administrations in rabbits, it has been shown that atropine has good ocular bioavailability via both transcorneal and transconjunctival-scleral routes [ 59 ]. Unfortunately and to the best of our knowledge, atropine metabolism in the eye has not been studied despite there being a clear incentive to do so, like for other drugs [ 60 ]. There is therefore very little information available about the possibility of the natural formation of tropic acid in the eye after atropine topical application or, as stated previously, about tropic acid’s ophthalmic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…During ophthalmic administrations in rabbits, it has been shown that atropine has good ocular bioavailability via both transcorneal and transconjunctival-scleral routes [ 59 ]. Unfortunately and to the best of our knowledge, atropine metabolism in the eye has not been studied despite there being a clear incentive to do so, like for other drugs [ 60 ]. There is therefore very little information available about the possibility of the natural formation of tropic acid in the eye after atropine topical application or, as stated previously, about tropic acid’s ophthalmic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Analytical challenges and sample availability have led to questions regarding how, why, and when it is appropriate to study ocular metabolism in vivo and in vitro (Argikar et al, 2017b). The review notes a resurgence in xenobiotic ocular metabolism, yet a comprehensive in vitro model to study the eye for metabolism and subsequent transport is not available as compared to the way one would traditionally characterize hepatic metabolism.…”
Section: In Vitro Models Of Ocular Metabolismmentioning
confidence: 99%
“…The model can also be used in lead optimization to drive structure-metabolism relationships by asking the right question at the right time. Examples at both ends of the drug discovery process may expand the way industry studies new ophthalmic treatments (Argikar et al, 2017b;Khojasteh et al, 2017).…”
Section: Models Of Ocular Drug Disposition and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Nutrients and drugs are actively or passively transported through the corneal epithelial barrier, followed by their intracellular metabolism, modification, and secretion of the corresponding metabolites. Although many metabolic pathways (e.g., oxidative, hydrolytic, reductive, and conjugative pathways) [3,4] and transporters [5,6] in the cornea have been investigated, the spatiotemporal mechanisms of the in situ metabolism and transportation of drugs through the human corneal barrier are barely known, owing to the technical difficulties in the current corneal experimental platforms as well as the lack of analytical tools that non-invasively enable longitudinal metabolome monitoring in small volumes. [7,8] Moreover, while the current in vitro corneal models that use cell-culture inserts (e.g., a transwell system) have been investigated, they only provide a two-dimensional structure of the corneal epithelial cells, which is physiologically different that in the cornea.…”
Section: Introductionmentioning
confidence: 99%